Nanostructured electrocatalysts for proton exchange membrane fuel cells (PEMFCS) - Wang, Shuangyin (2010)
The research work presented in this thesis is focused on the synthesis and characterization of nanostructured electrocatalysts for fuel cell reactions. “Firstly, a novel noncovalent functionalization method has been successfully developed to modify carbon nanotubes (CNTs) as electrocatalyst supports. The physicochemical characterizations and activity testing for methanol electrooxidation have been performed. We found the noncovalent functionalization method could significantly improve the dispersion and distribution of Pt (or PtRu) nanoparticles (NPs) supported on CNTs while preserving the perfect structure of CNTs, which resulted in the increased electrochemical active surface area and improved catalytic activity for methanol electrooxidation of Pt nano-electrocatalysts. Secondly, the as-developed noncovalent functionalization method could effectively equip carbon nanotubes with the specified surface functional groups. By choosing some characteristic polyelectrolytes, four given functional groups were introduced on the CNT surface, followed by the deposition of Pt NPs. The spectroscopic characterization, DFT calculation, and electrochemical testing demonstrated that the four different functional groups on CNTs as Pt supports had significantly different effect on the electronic properties and electrocatalytic activity for methanol oxidation on Pt NPs. It is proposed that the negatively charged functional groups could donate electrons to Pt surface, leading to weakened chemical adsorption energy with carbon monoxide (CO, a poisonous intermediate generated during the methanol electrooxidation), and thus improve catalytic performance for methanol electrooxidation. Thirdly, the combination of the polyol reduction method and the seed-mediated growth method could effectively load Pt NPs on CNTs with a wide range of Pt loadings (10 wt% ~ 93 wt %). As Pt loading on CNTs increases, both the interconnectivity and the electrocatalytic activity of Pt NPs increase gradually. The correlation between the electrocatalytic activity and the interconnectivity of Pt NPs is proposed. Our results illustrated that interconnected Pt NPs as electrocatalysts are more electrochemically active than the isolated Pt NPs.